2013
DOI: 10.1128/mbio.00271-13
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Severe Acute Respiratory Syndrome Coronavirus-Induced Acute Lung Injury

Abstract: Systems biology offers considerable promise in uncovering novel pathways by which viruses and other microbial pathogens interact with host signaling and expression networks to mediate disease severity. In this study, we have developed an unbiased modeling approach to identify new pathways and network connections mediating acute lung injury, using severe acute respiratory syndrome coronavirus (SARS-CoV) as a model pathogen. We utilized a time course of matched virologic, pathological, and transcriptomic data wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
317
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(339 citation statements)
references
References 62 publications
7
317
0
15
Order By: Relevance
“…In a previous study, 9 Gralinski et al investigated viral pathogenesis and identified a novel host pathway involved in severe acute respiratory syndrome (SARS)‐coronavirus disease progression. Their data suggest that dysregulation of the urokinase pathway during SARS‐coronavirus infection contributes to more severe lung pathology and that plasminogen activator inhibitor‐1 plays a protective role following infection.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, 9 Gralinski et al investigated viral pathogenesis and identified a novel host pathway involved in severe acute respiratory syndrome (SARS)‐coronavirus disease progression. Their data suggest that dysregulation of the urokinase pathway during SARS‐coronavirus infection contributes to more severe lung pathology and that plasminogen activator inhibitor‐1 plays a protective role following infection.…”
Section: Resultsmentioning
confidence: 99%
“…Although we have no evidences to favor any of these possibilities, PLASMIN, is a serine protease not only implicated in fibrinolysis but also in many other matrix protein breakdowns [25], which could include some of the rhabdoviral proteins. On this respect, serpine1 knock-out mice has shown that serpine1, tpa and plg are implicated in controlling coronavirus infections in mammals [26]. However, in coronavirus [26] and in yellow fever [27] infections, serpine1 levels were upregulated contrary to what occurred in fish rhabdoviruses.…”
Section: Inhibition Of Vhsv Infection In Vitro Could Only Be Obtainedmentioning
confidence: 99%
“…On this respect, serpine1 knock-out mice has shown that serpine1, tpa and plg are implicated in controlling coronavirus infections in mammals [26]. However, in coronavirus [26] and in yellow fever [27] infections, serpine1 levels were upregulated contrary to what occurred in fish rhabdoviruses. We can speculate that a dramatic fighting between host and rhabdovirus could exist to control ser-pine1 transcript levels during the initial course of fish rhabdoviral infections.…”
Section: Inhibition Of Vhsv Infection In Vitro Could Only Be Obtainedmentioning
confidence: 99%
“…A significant elevation of inflammatory cytokine and chemokine levels was also detected in early infection compared to the healthy control group. CD8 + T cells and neutrophils were found to migrate to the lungs during the late stage of infection [25,26].…”
Section: Sars-covmentioning
confidence: 99%